The inclusion of the other in ourselves: reception and comprehension of refugees in Portugal - Vieira, Ana (2020)
The intensification of different types of migration movements during the last decades is an expression of growing interconnections at the global level. The so caleed "refugee crisis" is the most visible sign of this intensification. It currently challenges societies to rethink the processes of integrating those fleeing from humanitarian crises and wars. Portuguese civil society has pioneered the creation of a Refugee Support Plattform, aimed to adress the challenges associated with the arrival of refugee families. Within this platform, an e-learning course was created to help institutions and host families prepare for this task. In the article we first describe this course focusing our analysis on the relevance of this iniciative for institutions, families, and private citizens tha wish to welcome refugees in Portugal.